Analisis The Total Economics Value Of The Mangrove Forest Area In The Development Of Ecotourism In Langsa City, Aceh - Safuridar Safuridar; Salman Salman; Iqlima Azhar (Glosains: Jurnal Sains Global Indonesia, 2022)
Mangrove forest is one of the potential forest resources so that it has a very important role in coastal and marine ecosystems, especially coastal areas. The maintenance and management of mangrove ecosystems is a problem that must be faced together for the sake of the continuity and sustainability of mangroveforests. The purpose of this study was to analyze the magnitude of the potential direct and indirect benefits, the total economic value of the mangrove forest area in the ecotourism development of Langsa City. The analytical method used is the analysis of benefits and costs. For all types of functions and benefits of mangrove forest areas, the total economic value (TEV) is descriptively used. The results showed that the total value of economic benefits from the mangrove forest of Gampong Kuala Langsa, Aceh was Rp. 2.958.847.000,- of the month which was obtained from 1) the direct benefit value from fish, crabs, shrimp, shellfish and seafood processing was amounting to Rp. 213.710.000,- of the month, 2) The value of indirect economic benefits is Rp. 1.014.379.000,- of the month obtained from trading activities and renting boats. 3) The value of choice is Rp. 1.729.038.000, - of the month from biodiversity, 4) The value of being is Rp. 1.720.000, - of the month. There is a surplus of community consumers in their willingness to pay for the existence of mangrove forests of Rp. 2,705,054.12 of the month.